Potentialities and difficulties in nursing education during the COVID-19 pandemic - Claudia Capellari; Letícia Gross Herrmann; Dagmar Elaine Kaiser; Joel Rolim Mancia (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To know the potentialities and difficulties in Nursing teaching during the COVID-19 pandemic, in Rio Grande do Sul (RS). Method Cross-sectional study carried out with coordinators of 48 undergraduate Nursing courses in the state of RS, Brazil, between October 2020 and January 2021, using an electronic questionnaire sent to participants by email. Data analysis was performed using descriptive and inferential statistics. Results It was highlighted, as potentialities, the expansion in handling information and communication technologies (87.5%), increased creativity (79.2%) and diversification of methodologies (77.1%). As difficulties, the reduction of skills training (75.0%), less student/professor/colleagues interaction (70.8%) and reduction of interpersonal relationships (64.6%). Conclusion If, on the one hand, difficulties were identified, such as the reduction of skills training and interpersonal relationships, on the other hand, potentialities related to new technologies and teaching methods signal disruptive and irreversible changes in Nursing education.